Physical Work Environment, Shift Work, and Mental Workload as Determinants of Occupational Stress among Locomotive Depot Workers - Rochmah, Ainur; Lestantyo, Daru; Wahyuni, Ida (Jurnal Penelitian Kesehatan SUARA FORIKES, 2026)
Locomotive depots are responsible for maintaining locomotives to ensure smooth railway operations. Inspection and maintenance workers play a direct role in this process and may be exposed to occupational stress due to various work-related factors. This study aimed to analyze factors associated with occupational stress among inspection and maintenance workers. A cross-sectional design was employed with total sampling of all 35 workers in the inspection and maintenance unit. Data were collected using the Work Stress Scale, physical work environment perception questionnaire, work relationship questionnaire, and NASA Task Load Index. Data were analyzed using the Spearman rank test. Most workers were middle-aged (65.7%), had good perceptions of the physical work environment (51.4%), and reported good work relationships (65.7%). More than half worked in shifts (57.1%) and had moderate mental workload (51.4%), while 34.3% experienced moderate levels of work stress, indicating that not all workers experienced stress. Significant associations were found between physical work environment perception (p = 0.006), shift work (p = 0.012), and mental workload (p = 0.001) with occupational stress. In conclusion, physical work environment, shift work, and mental workload are key determinants of occupational stress among locomotive depot workers. Effective management of these factors is essential to prevent adverse impacts.Keywords: occupational stress; physical work environment; shift work; mental workload; locomotive depot workers